Expanding the therapeutic horizon in acute myeloid leukemia: The role of phosphoinositide-3-kinase-γ inhibition - Soumyajit Das; Mahendra Pratap Singh; Nishant Rai; Sanjit Sah (Iraqi Journal of Hematology)
Acute myeloid leukemia (AML) remains a formidable challenge due to its high relapse rate and limited therapeutic options. This study investigates the role of phosphoinositide-3-kinase-γ (PI3Kγ) in AML and explores the therapeutic potential of the PI3Kγ inhibitor, eganelisib, in preclinical models. Using genome-wide CRISPR interference screening, we identified PI3Kγ as a critical survival pathway in certain AML subsets. We demonstrated that inhibition of PI3Kγ with eganelisib disrupts oxidative phosphorylation, thereby impeding AML cell survival and proliferation. Notably, the combination of eganelisib with cytarabine showed enhanced efficacy, suggesting a synergistic interaction that improves treatment outcomes. These findings indicate that PI3Kγ is a viable therapeutic target in AML and that PI3Kγ inhibitors could be pivotal in overcoming treatment resistance and reducing relapse.